Edukasi Pencegahan dan Pengobatan Gastritis di Puskesmas Abepura - Oktliana Pasangka; Elisabet Bre Boli; Dwi Astuti; Hendry Kiswanto Mendroafa; Zusana A. Sasarari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Gastritis is a condition caused by inflammation of the stomach lining, often leading in pain and discomfort in the abdomen. Gastritis has become a growing concern, particularly in developing countries like Indonesia. Irregular eating habits, smoking, and frequent consumption of carbonated or alcoholic beverages can trigger gastritis. Additionally, the use of NSAID medications can also lead to the development of gastritis. The management of gastritis has evolved with advancements in diagnostic techniques and treatment options. An educational initiative was carried out at the Abepura Community Health Center. According to data on the top 10 diseases in 2023, gastritis was the most common non-communicable disease. This is likely due to Abepura sub-district being one of the areas with a high population density and activity level, influencing lifestyle choices. The purpose of the education was to help the community understand gastritis, its causes, prevention, and the correct use of medication. The method used was a participatory approach, targeting all visitors to the Abepura Health Center during the service activity. The conclusion of the service activity at the Abepura Health Center is that the community of Abepura now has a better understanding of proper prevention and management of gastritis.